Approaching Migrant Youth Marginalization through the Capabilities Approach: Methodological Proposals - Wassilios Baros; Georgia Manafi (Social Work and Society)
Adopting the capabilities approach and the terminology that has been respectively developed, we could assume that Amartya Sen's"capabilities" consist in the actual living that people manage to achieve (e"functionings") as a result of actual free will. Sen's freedom does not"only [depend on the] mere degree of the presence or absence of coercion or interference (from others)" (Otto and Ziegler 2006) but also on"the range of options a person has in deciding what kind of life to lead" (Dreze and Sen 1995, 10). In his book, Identity and Violence, Sen, without explicitly connecting the capabilities approach with his views on"genuine multiculturalis"Â  (Sen 2007), in fact, introduces this extended conception of freedom in the way we examine identity matters. Since freedom becomes perceptible as the range of options a person has, concerning the kind of life he wishes to live, cultural freedom can be defined through the concept of the multiplicity of belonging. In other words, cultural freedom constitutes itself a capability, which is realized when nothing and no one, not even myself, can tie me down to a kind of cultural rigidity that tends to exclude and marginalize me. This latent connection of"capabilities" with"multiple identities" (Sen 2007) challenges us to search for the contribution Sen's approach could have in the understanding and confrontation of issues concerning migrants, away from theoretical patterns that overemphasize the cultural otherness as an impediment to inclusion. Besides, Sen himself, without of course focusing exclusively on migrants, has already approached the matter of social exclusion with terms of his capabilities approach (Sen 2000).